How to effectively Teach a short Course - Skov, Thomas (Improving University Science Teaching and Learning, 2023)
How do I effectively teach a short course? In a short course I will probably have a more mixed audience – how do I cope with that? These two questions will be discussed here based on my experiences from teaching the same short course three times a year over the last five years. I will mainly touch upon how amendments to the short course can be justified from a didactical perspective, but also describe some didactical techniques that are also useful for longer courses. Through my experience and by participating in Adjunktpædagogikum I have realized how the use of well selected didactical techniques can improve the learning outcome significantly and here I reflect on the impact of a modified teaching style. “In a short course don’t be a stranger – make the audience feel good, be congenial and tell a few jokes”